Sejarah Bentor Sebagai Icon Kota Pematang Siantar - Nizam, Muhammad Khairul; Lubis, Afifi Takrimi; Haryanto, Reza; Hasiando; Siregar, Yusra Dewi (Ikatan Da'i Indonesia, 2024)
Economic and social development in urban areas is highly dependent on an effective transportation system to support population mobility and economic growth. One form of transportation that is characteristic of Pematangsiantar City is the BSA (Birmingham Small Arms) motorbike cart, which has a rich history and has become a tourist icon that attracts the interest of many people. However, the decline in the number of BSA motorbike carts in Pematangsiantar City is a concern, due to factors such as increasing prices, competition from other types of transportation, and lack of support from the local government. To maintain the sustainability of BSA motor carts as part of the city's identity and cultural heritage, as well as utilizing tourism potential to drive the local economy, collaborative efforts are needed between motor cart owners and drivers, the government and the community. This research uses a qualitative approach, with a case study method, to explore understanding and experiences regarding BSA motorbike carts in Pematangsiantar City, with the hope of contributing to the understanding of the use, challenges and potential of BSA motorbikes in the context of intra-city transportation in Pematangsiantar City.